Disease Prediction with a Maximum Entropy Method (CSIAM Transactions on Life Sciences, 2025)
In this paper, we propose a maximum entropy method for predicting disease risks. It is based on a patient’s medical history with diseases coded in International Classification of Diseases, tenth revision, which can be used in various cases.The complete algorithm with strict mathematical derivation is given. We also presentexperimental results on a medical dataset, demonstrating that our method performswell in predicting future disease risks and achieves an accuracy rate twice that of thetraditional method. We also perform a comorbidity analysis to reveal the intrinsic relation of diseases.